2012
DOI: 10.1097/pas.0b013e31825fa931
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D1 as a Diagnostic Immunomarker for Endometrial Stromal Sarcoma With YWHAE-FAM22 Rearrangement

Abstract: Endometrial stromal sarcoma (ESS) characterized by YWHAE-FAM22 genetic fusion is histologically higher-grade and clinically more aggressive than ESS with JAZF1-SUZ12 or equivalent genetic rearrangements, hence it is clinically important to recognize this subset of ESS. To identify diagnostic immunomarkers for this biologically-defined ESS subset, we compared gene expression profiles from YWHAE-FAM22 ESS, JAZF1-rearranged ESS and uterine leiomyosarcomas. These studies showed consistent upregulation of cyclin D1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
153
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 181 publications
(168 citation statements)
references
References 37 publications
10
153
0
Order By: Relevance
“…Cyclin D1 immunohistochemistry should be useful in these cases because YWHAE-NUTM2A/B endometrial stromal sarcoma consistently shows diffuse (470%) and strong nuclear immunopositivity of the high-grade component. 6 To further explore the potential of KIT as therapeutic target in YWHAE-NUTM2A/B endometrial stromal sarcomas, we interrogated KIT mutations in KIT-positive YWHAE-NUTM2A/B endometrial stromal sarcomas, and found no mutations involving KIT or other receptor tyrosine kinases including PDGFRA. In the absence of an activating mutation, the rationale for targeting YWHAE-NUTM2A/B endometrial stromal sarcomas with imatinib and/or other small-molecule inhibitors of receptor tyrosine kinases remains questionable.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyclin D1 immunohistochemistry should be useful in these cases because YWHAE-NUTM2A/B endometrial stromal sarcoma consistently shows diffuse (470%) and strong nuclear immunopositivity of the high-grade component. 6 To further explore the potential of KIT as therapeutic target in YWHAE-NUTM2A/B endometrial stromal sarcomas, we interrogated KIT mutations in KIT-positive YWHAE-NUTM2A/B endometrial stromal sarcomas, and found no mutations involving KIT or other receptor tyrosine kinases including PDGFRA. In the absence of an activating mutation, the rationale for targeting YWHAE-NUTM2A/B endometrial stromal sarcomas with imatinib and/or other small-molecule inhibitors of receptor tyrosine kinases remains questionable.…”
Section: Discussionmentioning
confidence: 99%
“…1,3 Hematoxylin-and eosin-stained and -unstained slides that showed high-grade round/epithelioid cell component only, 6 low-grade spindle cell component only 2 or both areas 6 were available for the study. This study was approved by the institutional research boards.…”
Section: Study Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…71 In the highgrade areas, the tumor cells are small with very brisk mitotic activity and are associated with a prominent sinusoidal vasculature. Although CD10, ER, and PR are typically positive in low-grade endometrial stromal sarcomas, it is important to keep in mind that the high-grade component is typically negative for these markers (but diffusely positive for cyclin D1) 72 and that very commonly leiomyosarcomas express CD10 as well as ER and PR. [73][74][75][76][77][78] Thus, when using immunohistochemistry, a panel rather than a single marker that includes desmin and h-caldesmon is necessary.…”
Section: Tumor Cell Necrosismentioning
confidence: 99%
“…It is important to be aware that the low-and high-grade components have a different immunohistochemical profile (Figures 7e and f). 50 The low-grade component is typically positive for CD10, ER, and Figure 6 Uterine tumor resembling ovarian sex-cord tumor (UTROSCT). These unusual tumors are composed of epithelial-like cells that recapitulate the architecture patterns described in ovarian sex-cord stromal tumors (a).…”
Section: Distinction Of Lgess With Sex Cord-like Differentiation Frommentioning
confidence: 99%